Parent and Teacher Cooperation in Improving Learning Quality in the Covid-19 Pandemic Era: A Site Study of the Madrasah Ibtidaiyah in Trenggalek City - Muhamad Zaini; Nur Efendi; Elma Fuadah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Indonesia is one of the countries affected by the spread of the COVID-19 virus, and education is no exception. The government enforces a policy that all learning activities are carried out at home with an online learning system. Thus, a collaboration between parents and teachers aims to improve learning quality in the COVID-19 pandemic era. Second, the collaboration between parents and teachers also aims to make children receive subject matter, develop their abilities, and grow their character. This study took data from MI Masaran I and MI Tawing III GUPPI Trenggalek, with the research data sources being principals, teachers, and student's parents. Collecting data used participant observation, documentation, and in-depth interviews. This study employed a qualitative approach with the type of site study and multi-site study. The findings of this study revealed that parents were involved in learning, established good communication to solve problems, engaged in materials and actions, provided facilities to support learning, and teachers visited students' homes and invited parents to school. With the results of this research, it is hoped to improve the students’ development and ability so that the educational goals in Indonesia continue to run as expected.